The Effect of ( K.W.L.H) Strategy on the Second Grade Intermediate Students’ Achievement in Arabic Language Grammar and Improving Their Cognitive Motivation. (Journal of the College of Basic Education, 2022)
The current research aim is to achieve, The Effect of ( K.W.L.H) Strategy on the second grade intermediate students’ achievement in Arabic Language Grammar and its effect on improving their cognitive motivation. The researcher adopted the experimental design, an experimental group and control group with an experiment has been designed only. The population of the study includes 2nd grade intermediate male students in the Directorate General of Education Baghdad Al-Rusafa /3. The total number were (9479) , distributed as (93) secondary and intermediate schools. The Hassan Shehata’s school had chosen, It has (135) students. The sample subjects are 60 students for the experimental and control groups. The researcher derived the behavior objectives of the Arabic language grammar topics for the second course includes (9) subjects. The test consists of (30) items which multiple- choice items, then he built the cognitive motivation scale for ( Shallal and Mahdi 2013), The researcher applied his experience in second course during academic year (2018- 2019), for (9) weeks. After applying the experiment the statistical analysis of the result showed the experimental group who is taught by ( K.W.L.h) strategy is better than the control group who is taught by the traditional way, As the result showed the experimental group is higher in cognitive motivation than the control group.